A case study of the HNA group cross-border M&A strategy. Issue 9 (12th September 2016) - Xiao, Ying; Thomas, Mark
Abstract : Purpose: The purpose of this article is to outline the reasons for the success of the Chinese HNA Group in the development of its international strategy. Design/methodology/approach: The article adopts a critical single case study method approach. Findings: The HNA Group has been highly successful using cross-border merger and acquisitions (M&As) as a platform for growth. However, Chinese companies are facing more difficulties compared to their international competitors in cross border M&A deals and are paying a higher premium for that. Even HNA Group, a veteran player in the international capital market, may not be exempted from the skeptics toward China money. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.